Fibril morphology and tendon mechanical properties in patellar tendinopathy: effects of heavy slow resistance training - Kongsgaard, Mads; Qvortrup, Klaus; Larsen, Jytte; Aagaard, Per; Doessing, Simon; Hansen, Philip; Kjaer, Michael; Magnusson, S Peter (The American journal of sports medicine, 2010)
Patellar tendinopathy is characterized by pathologic abnormalities. Heavy slow resistance training (HSR) is effective in the management of patellar tendinopathy, but the underlying functional mechanisms remain elusive. To investigate fibril morphology and mechanical properties in patellar tendinopathy and the effect of HSR on these properties. Cohort study; Level of evidence, 2. Eight male patients with patellar tendinopathy completed 12 weeks of HSR. Nine healthy subjects served as controls. Assessments were conducted at baseline and at 12 weeks. Patients assessed symptoms/function and maximal tendon pain during activity. Tendon biopsy samples were analyzed for fibril density, volume fraction, and mean fibril area. Tendon mechanical properties were assessed using force and ultrasonography samplings. Patients improved in symptoms/function (P = .02) and maximal tendon pain during activity (P = .008). Stiffness and modulus of control and tendinopathy tendons were similar at baseline. Stiffness remained unaffected in control tendons (3487 +/- 392 to 3157 +/- 327 N/mm, P = .57) but declined in tendinopathic tendons at 12 weeks (3185 +/- 187 to 2701 +/- 201 N/mm, P = .04). At baseline, fibril volume fraction was equal, fibril density smaller (P = .03), and mean fibril area tended to be higher in tendinopathy versus controls (P = .07). Fibril morphology remained unchanged in controls but fibril density increased (70% +/- 18%, P = .02) and fibril mean area decreased (-26% +/- 21%, P = .04) in tendinopathic tendons after HSR. Fibril morphology is abnormal in tendinopathy, but tendon mechanical properties are not. Clinical improvements after HSR were associated with changes in fibril morphology toward normal fibril density and mean fibril area. Heavy slow resistance training improved the clinical outcome of patellar tendinopathy, and these improvements were associated with normalization of fibril morphology, most likely due to a production of new fibrils.